O (não) falar português: os desafios de um acolhimento linguístico a imigrantes e refugiados venezuelanos - Borges, Ana Júlia Fernandes Braga (2024)
This study investigates how the language barrier impacts the integration of Venezuelan immigrants in Brazil, the most significant in Americas (Jarochinski-Silva et al. 2021), based on the hypothesis that communication in Portuguese represents one of the first difficulties that Spanish-speaking immigrants face when migrating to Brazil. The guiding question of this dissertation is: "Is it possible to create an environment of welcome that facilitates integration, using language as a tool for inclusion, without requiring migrants to abandon their customs and ways of being?". Through a qualitative methodology, semi-structured interviews were conducted with six Venezuelans, recruited using snowball sampling, alongside participant observation as a teacher of PLAc (Portuguese as a Language of Welcome) and consultation of quantitative data to characterize the migration flow. Although this group is not a sample, and therefore no broad claims are made about the characteristics of this flow, the reported experiences indicate that Portuguese, despite being a barrier at the beginning, can become a bridge, a tool for integration. This dissertation contributes to sociological studies on migration and otherness by discussing the role of language in the processes of welcoming and integration, and how it intersects with issues of work, housing, access to health rights and services, and connects with questions of identity and translation (Hall, 2020)